Laboratory Blood-Based Testing for Lyme Disease at a National Reference Laboratory: A 7-Year Experience (2010-2016). Issue 1 (15th April 2019) - Lee-Lewandrowski, Elizabeth; Chen, Zhen; Branda, John; Baron, Jason; Kaufman, Harvey W
ABSTRACT: Objectives: We evaluated trends in Lyme disease (LD) testing at a national reference laboratory. Methods: LD screening enzyme immunoassay and Western blot testing data performed at Quest Diagnostics during 2010 to 2016 were analyzed nationally and at the state level. Results: Overall, 593, 800 (11.3%) results were positive of 5, 255, 636 tests. There was an increase in the rate of positivity over the last 2 years of the study and an increase in the number of positive tests in 2016. Positive tests were observed in all 50 states and the District of Columbia. New York had the most positive tests, whereas Connecticut had the highest positivity rate when normalized to state populations. Some states with historically low rates of LD (eg, Texas, Florida, and California) showed significant increases in testing and positivity rates over time. Conclusions: LD testing and positivity have increased in recent years, including in states not historically associated with the disease.